Bioimpedance in Biomedical Applications and Research (Springer International Publishing, 2018)
This book is based on the best contributions to the advancement of bioimpedance knowledge and use from the Latin American Congress series, CLABIO. Basic bioimpedance facts as well as promising and original contributions to bioimpedance theory and applications are presented, giving the reader stimulating material for reflection, decision making, and further experiments. Contributions come from a diverse international pool of experts and address topics on electrode and skin impedance modelling, tomography, spectroscopy, instrumentation, and clinical applications.